Curriculum design, development and implementation in a transnational higher education context. (19th August 2014) - Tian, Xuemei; Blessinger, Patrick
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose To report on an applied research project involving the application of core learning and pedagogical theory to a specific unit in a transnational undergraduate business course. Design/methodology/approach The project sought to collect data and learning experiences based upon intensive literature reviews and a combined quantitative-qualitative research method. Established research constructs and recent lessons from the literature were applied to the two year reform cycle of an undergraduate business unit. Findings The findings validated the research constructs and frameworks employed and reinforced the case for enhancing the nexus between alignment, student motivation, active learning and the international-transnational perspective. Despite initiatives to engender openness and interactivity in the classroom, including dynamic and innovative approaches to communication and content delivery neither the operation of the class nor the eventual performance of the students lived up to expectations. Research limitations/implications The research was limited to the experiences of three different cohorts of students on the same unit over a two year period. Implications are that the same research method and approach are valid for other units either in the same faculty or across faculties. Practical implications Serves as an example of what can and cannot be achieved by academics seeking to align their teaching and research activities on a relatively modest basis. Originality/value While not entirely original, the paper adds value in the form of 'lessons learned' from an applied classroom-based research project.